Assessing the impact of digital marketing optimization on the self-sustainability of agrotourism in Sumbergedang Village - Sujono Sujono; Ratih Juliati; Risky Angga Pramuja; Mohamad Nurul (Journal of Enterprise and Development (JED), 2023)
Purpose — This research delves into the evaluation of the impact of digital marketing optimization on the self-sustainability of agrotourism in Sumbergedang Village. The study aims to determine how the strategic utilization of digital marketing tools and techniques contributes to the overall sustainability of the agrotourism sector in this village.Method — To achieve this objective, a comprehensive analysis was conducted, considering various aspects such as online promotional efforts, social media engagement, and technology adoption among agrotourism businesses. Data was collected through surveys, interviews, and observation of agrotourism activities in the village.Result — Preliminary findings indicate a positive correlation between the implementation of effective digital marketing strategies and the sustainability of agrotourism ventures in Sumbergedang Village. Businesses that actively engaged in digital marketing activities experienced increased visibility, improved customer engagement, and a higher likelihood of repeat visits by tourists. These factors, in turn, have contributed to the self-sustainability of the agrotourism sector by generating steady income streams and supporting local livelihoods.Contribution — This impact analysis sheds light on the crucial role of digital marketing in fostering self-sustaining agrotourism in Sumbergedang Village. It underscores the importance of leveraging digital tools to enhance the visibility and appeal of agrotourism offerings, ultimately benefiting the local economy and promoting the long-term viability of this sector.